Wandel des japanischen (Berufs-)Bildungssystems von der "Kultivationspädagogik" zur "Fachschulung"? - Eswein, Mikiko [Verfasser] (My University, 2016)
"A good way to describe the change of the (vocational) education system during the transition to modern society, is using the terms 'formal rationalisation' (increased efficiency) and 'material rationalisation' (subjects' participation). In the process of increasing the economic efficiency in Japan's Confucianist society, general education won through in the context of cultivative education (Kultivationspädagogik), rather than technical training (Fachschulung). However, professional knowledge has become more and more important in Japan, too. The Japanese solution is a hybrid formed by inclusions of parallel, routinised, charismatic education (Einschlüsse paralleler veralltäglichter charismatischer Erziehung) within cultivative education. In order to promote democratisation in terms of subjects' participation in governance, and as a specific measure for enabling disadvantaged younger people to enter regular employment in large companies, professional qualifications (bearing support functions in Japan) have been established which may be acquired at the companies' request after recruitment - besides the advancement of general education." (Authors' abstract, BIBB-Doku)
Keywords: S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; G 2.3.5 Wirtschaftsstrukturwandel; S 3.2 Unternehmen und Behörden; I 2.3.4 Asien; Bildungssystem; Berufsbildungssystem; Bildungsreform; Demokratisierung; Strukturwandel; Unternehmen; Japan